Defining Creativity: Don't We Also Need to Define What Is Not Creative?. (25th January 2016) - Simonton, Dean Keith
Abstract: I argue that any attempt to define creative ideas cannot fully succeed without also defining uncreative ideas. This argument begins by defining three parameters that characterize a potentially creative thought: the idea's initial probability ( p ), the final utility ( u ), and the creator's prior knowledge of that utility ( v ). The three parameters then lead to a three‐criterion multiplicative definition of personal creativity, namely, c = (1 − p ) u (1 − v ), where the first factor indicates originality and the third factor surprise . Although creativity can only maximize as originality, utility, and surprise all approach unity, the same definition indicates that there are seven different ways that creativity can minimize. These alternatives were identified as (a) routine, reproductive, or habitual ideas, (b) fortuitous response bias, (c) irrational perseveration, (d) problem finding, (e) rational suppression, (f) irrational suppression, and (g) blissful ignorance. If the third parameter v is omitted, then the number of creative and noncreative outcomes reduces to just four, making creativity indistinguishable from irrational suppression. The alternative outcomes are then illustrated using the classic two‐string problem. Besides providing a more finely differentiated conception of creativity failures, the definition has critical implications regarding the processes and procedures required to generate highly creative ideas.